Optimal tracking control of a trajectory planned via fuzzy reactive approach for an autonomous mobile robot. (22nd February 2018) - Akka, Khaled; Khaber, Farid
This article deals with the design of an optimal tracking controller for a wheeled mobile robot. The tracking control can be performed to track either a given or a planned trajectory. In our study, an improved linear quadratic tracker is adopted to track a path planned using an improved reactive approach that combines the dynamic window with the fuzzy logic to make the robot movement toward the target faster, smoother, and safer whatever the complexity of the environment. The fuzzy logic is used to dynamically adjust the weights of the terms included in the dynamic window objective function according to different environmental scenarios. Simulation results of the path planning and the tracking control prove that the proposed approaches are significantly superior to the conventional ones.